Why is ethics important in history education? A dialogue between the various ways of understanding the relationship between ethics and historical consciousness - Silvia Edling; Heather Sharp; Jan Löfström; Niklas Ammert (Routledge, 2025)
In light of current tendencies, where appreciating plurality and uphold everyone’s equal value is being questioned from different directions, there is arguably a need to revive the ethical dimension of history education as a way of learning about difficult histories, including traumatic pasts. Since the 1970s historical consciousness has played an important role in articulating an approach to history with an ethical mindset. Although many theories suggest that there is a connection between ethics and historical consciousness, a deeper understanding of this link is generally absent. This article discusses selected key texts by major researchers in the field, namely Rüsen, Seixas and Morton, Chinnery, and Simon. Their texts reflect four different perspectives, which, in this article are kept in dialogue with one another as a way of stimulating and sharpening ethical understanding and judgement in history education through the theoretical toolbox offered.